Sentar las bases del orden fiscal. Los presupuestos provinciales de Santa Fe (Argentina, 1855-1873) - Evangelina De los Ríos (Res Gesta, 2018)
The objective of this article is to examine the budgets of the province of Santa Fe (Argentine) between 1855 and 1873. It will be argued that a budget is not a simple estimate of expenses, for the government that elaborates it constitutes the moment of definition of its economic policy. The way in which it was intended to invest the resources - regardless of whether those decisions were remote or not to the real situation of the finances - presents itself like a good observatory from which to study the form in which it was sought to construct that State. This research focuses on two aspects: the composition of the budget items, on the one hand, and the debates that have taken place within the Legislative Assembly on this issue, on the other. This analysis at the local level offers an adequate conceptual framework to deepen a historiographical discussion about the state formation processes in fiscal key.